Social Protection for the Informal Economy : Operational Lessons for Developing Countries in Africa and Beyond - Guven, Melis (World Bank, Washington, DC, 2021)
The informal economy in Africa is large and diverse, and it is the main source of employment in the region. It is projected to grow and create more jobs. The informal economy is well established in the region, but it also faces a host of development challenges. It is characterized by low human capital and productivity compared with the formal economy and is typically associated with limited access to resources such as electricity, finance, land, and public services. People who work in the informal economy are usually more susceptible to short-term shocks and the more catastrophic consequences of idiosyncratic shocks (acute short-term crises, such as illness) and covariate shocks (chronic or widespread shocks affecting entire communities). These vulnerabilities are exacerbated because these people ordinarily have limited avenues to formal financial institutions or risk mitigation instruments. Women are more likely to work in the informal economy in Africa and are therefore also more likely to experience precarious work environments. The COVID-19 pandemic highlighted the vulnerabilities of the vast informal economy, especially in urban areas. Social protection cash transfers provided an essential platform for delivering assistance in response to the COVID-19 shock in the Africa region. In addition to macroeconomic measures to support economic recovery, governments needed to limit the damage to livelihoods, especially in the informal economy. Many governments in the region added to their capacity to extend coverage with innovations in targeting and delivering payments by leveraging technology and using big data. In many cases, registration was carried out using mobile technology. Some governments opted to implement more direct registration processes by creating dedicated websites or relying on informal economy associations. These swift responses were success stories in their own right, but they were undertaken essentially as a response to an urgent requirement to provide much-needed support to groups that lacked social protection and to prevent them from slipping into poverty. Governments allocated significant resources, typically through external financing (US6.1 billion dollars in additional spending in 30 countries across Africa).